Screening and brief interventions for hazardous and harmful alcohol use in probation services: A cluster randomised controlled trial protocol - Newbury-Birch, Dorothy; Bland, Martin; Cassidy, Paul; Coulton, Simon; Deluca, Paolo; Drummond, Colin; Gilvarry, Eilish; Godfrey, Christine; Heather, Nick; Kaner, Eileen; Myles, Judy; Oyefeso, Adenekan; et al. (BMC Public Health, 2009)
Background: A large number of randomised controlled trials in health settings have consistently reported positive effects of brief intervention in terms of reductions in alcohol use. However, although alcohol misuse is common amongst offenders, there is limited evidence of alcohol brief interventions in the criminal justice field. This factorial pragmatic cluster randomised controlled trial with Offender Managers (OMs) as the unit of randomisation will evaluate the effectiveness and cost-effectiveness of different models of screening to identify hazardous and harmful drinkers in probation and different intensities of brief intervention to reduce excessive drinking in probation clients. Methods and design: Ninety-six OMs from 9 probation areas across 3 English regions (the North East Region (n = 4) and London and the South East Regions (n = 5)) will be recruited. OMs will be randomly allocated to one of three intervention conditions: a client information leaflet control condition (n = 32 OMs); 5-minute simple structured advice (n = 32 OMs) and 20-minute brief lifestyle counselling delivered by an Alcohol Health Worker (n = 32 OMs). Randomisation will be stratified by probation area. To test the relative effectiveness of different screening methods all OMs will be randomised to either the Modified Single Item Screening Questionnaire (M-SASQ) or the Fast Alcohol Screening Test (FAST). There will be a minimum of 480 clients recruited into the trial. There will be an intention to treat analysis of study outcomes at 6 and 12 months post intervention. Analysis will include client measures (screening result, weekly alcohol consumption, alcohol-related problems, re-offending, public service use and quality of life) and implementation measures from OMs (the extent of screening and brief intervention beyond the minimum recruitment threshold will provide data on acceptability and feasibility of different models of brief intervention). We will also examine the practitioner and organisational factors associated with successful implementation. Discussion. The trial will evaluate the impact of screening and brief alcohol intervention in routine probation work and therefore its findings will be highly relevant to probation teams and thus the criminal justice system in the UK. © 2009 Newbury-Birch et al; licensee BioMed Central Ltd.
Keywords: Criminal Justice; Alcohol Intervention; Probation Office; Standard Drink; Brief Intervention